PSYCHOMETRIC TESTS APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Iwan Setiawan Rahman; Rahayu Noveandini, SKom. MM (Jurnal Sistem Informasi, 2005)
Despite the enormous capacity of the human brain, we only use an average of two percent of our potential brain power, we therefore have the potential to expand ourbrainpower and testing (testing) on a regular basis as a key method that brain power.Psychometric tests covering subjects such as personality tests which includelateralitas tests, creativity tests are based on patterns of thoughts, feelings, attitudesand knowledge, and measure the range of human aspects. Intelligence test a test usedto measure the level of thinking ability a person.One of the problems that arise in every human being has a personality that hasdifferent capabilities, including lateralitas, creativity and intelligence. In this case thecharacteristics that distinguish ourselves with others.Based on these problems the writer tries to pick and find a solution to give a practicalillustration through the questions will be answered in psychometric tests. In writingthis scientifically demonstrated several ways to solve these malasah, among others,by using application analysis, design programs, ie algorithms programs, menustructure, program flowchart, design and configuration of input and output of thecomputer as well as discussion of these issues.